RANCANG BANGUN GAME ADVENTURE 3D PENGENALAN ALPHABET PADA ANAK USIA DINI - Tegar Mahendra Nur Hidayat; nu Azizah; Cindy Taurusta (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
This research develops a 3D adventure game application as a learning media to assist TK At-Taqwa students in recognizing and memorizing alphabet letters. Based on the concept that effective education starts at an early age, the application is designed using the Multimedia Development Life Cycle (MDLC) method. The research stages include observation, design, development, and application testing. Results show that the game is effective in enhancing students' ability to recognize and memorize alphabet letters, as evidenced by the User Acceptance Test (UAT) averaging 85.5%, rated "Very Good". With engaging interfaces, supportive background music, and challenging game levels, this application provides a fun and effective learning experience for early childhood education. Thus, the game serves as an effective alternative for alphabet learning in kindergartens, addressing challenges of boring learning methods and student motivation issues.